Our dream : - Granzow, Sandra (Oxford University Press, 2000)
This vivid photo book opens with a preface by World Bank Group president, James D. Wolfensohn. Behind the photos, the human style, and the quotes from Bank Group staff and country counterparts, are real stories about poverty that depict 18 projects from around the world where the Bank and its partners have made a demonstrable impact. The stories were researched and written with extensive cooperation from the project and country teams. Photographs were provided by the World Bank Group staff in the field, in-country photographers and the Bank Group's photo archives.